Critical percolation in the dynamics of the 2D ferromagnetic Ising model. (6th November 2017) - Blanchard, Thibault; Cugliandolo, Leticia F; Picco, Marco; Tartaglia, Alessandro
Abstract: We study the early time dynamics of the 2 d ferromagnetic Ising model instantaneously quenched from the disordered to the ordered, low temperature, phase. We evolve the system with kinetic Monte Carlo rules that do not conserve the order parameter. We confirm the rapid approach to random critical percolation in a time-scale that diverges with the system size but is much shorter than the equilibration time. We study the scaling properties of the evolution towards critical percolation and we identify an associated growing length, different from the curvature driven one. By working with the model defined on square, triangular and honeycomb microscopic geometries we establish the dependence of this growing length on the lattice coordination. We discuss the interplay with the usual coarsening mechanism and the eventual fall into and escape from metastability.